2013
DOI: 10.1371/journal.pone.0070308
|View full text |Cite
|
Sign up to set email alerts
|

HSV-2 Regulates Monocyte Inflammatory Response via the Fas/FasL Pathway

Abstract: Monocytic cells represent important cellular elements of the innate and adaptive immune responses in viral infections. We assessed the role of Fas/FasL in promoting monocyte apoptosis during HSV-2 infection by using an in vitro model based on the murine RAW 264.7 monocytic cell line and an in vivo murine model of HSV-2 infection applied to C57BL6, MRL-Faslpr/J (Fas−/−) and C3-Faslgld/J (FasL−/−) mice. HSV-2 infection of the monocytic cell line led to early induction of apoptosis, with no protective expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
5
28
2
Order By: Relevance
“…In our study, we found significantly decreased total numbers of NK cells in the vaginal tissue at 7 but not at 3 day of infection. We have previously shown that decreased mobilization of NK cells into the vaginal tissues of Fas-and FasL-deficient mice during HSV-2 infection may be due to the monocytes producing significantly less CXCL9, CXCL10 and TNF-␣ than monocytes in the wild type mice (Krzyzowska et al 2013). Here, we also found significantly decreased percentage of NK cells with IFN-␥ expression, which can and WT (C57BL/6) mice.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In our study, we found significantly decreased total numbers of NK cells in the vaginal tissue at 7 but not at 3 day of infection. We have previously shown that decreased mobilization of NK cells into the vaginal tissues of Fas-and FasL-deficient mice during HSV-2 infection may be due to the monocytes producing significantly less CXCL9, CXCL10 and TNF-␣ than monocytes in the wild type mice (Krzyzowska et al 2013). Here, we also found significantly decreased percentage of NK cells with IFN-␥ expression, which can and WT (C57BL/6) mice.…”
Section: Discussionsupporting
confidence: 62%
“…as well as the total numbers of CD8+ T cells at 3 and 7 d.p.i. (Krzyzowska et al 2013). Here, decreased total counts of CD4+ T cells were followed by a significant decrease in the percentage of IFN-␥ expressing CD4+ T cells at 7 d.p.i.…”
Section: Lack Of Fas or Fasl During Hsv-2 Vaginal Infection Results Imentioning
confidence: 63%
See 3 more Smart Citations